Regioselective Arylboration of 1, 3‐Butadiene. Issue 3 (21st August 2019) - Bergmann, Allison M.; Sardini, Stephen R.; Smith, Kevin B.; Brown, M. Kevin
Abstract: A method for the regioselective 1, 2‐arylboration of 1, 3‐butadiene, a feedstock chemical, is reported. The reactions result in the formation of products that can be easily elaborated to other structures. The mechanistic details of this process are also discussed. Abstract :